2010
DOI: 10.1073/pnas.1007001107
|View full text |Cite
|
Sign up to set email alerts
|

Three-amino-acid-loop-extension homeodomain factor Meis3 regulates cell survival via PDK1

Abstract: Three-amino-acid-loop-extension (TALE) homeodomain proteins including Meis and Pbx families are generally recognized for their roles in growth and differentiation during vertebrate embryogenesis and tumorigenesis. Whereas genetic studies indicate that Pbx1 regulates the development and function of insulin-producing pancreatic β-cells, the role of Meis family members in β-cells is still unknown. Here we show that Meis3 is abundantly expressed in pancreatic islets and β-cells and that it regulates β-cell surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
0
24
2
Order By: Relevance
“…In support of this, overexpression of PDK1 has been implicated in the development of prostate and pancreatic cancer in vivo 25,[33][34][35] and has been shown to transform mouse mammary epithelial cells in vitro. 36 The mechanism of overexpression is unclear; it has been reported that Meis3 up-regulated PDK1 transcription; 37 however, in our microarray database of 205 AML patients we found no correlation between Meis3 and PDK1 mRNA expression which also correlated poorly with PDK1 protein levels (data not shown). This observation is in accord with our previous data that suggested that PDK1 overexpression in this context arises from a post-translation mechanism.…”
Section: Discussioncontrasting
confidence: 42%
“…In support of this, overexpression of PDK1 has been implicated in the development of prostate and pancreatic cancer in vivo 25,[33][34][35] and has been shown to transform mouse mammary epithelial cells in vitro. 36 The mechanism of overexpression is unclear; it has been reported that Meis3 up-regulated PDK1 transcription; 37 however, in our microarray database of 205 AML patients we found no correlation between Meis3 and PDK1 mRNA expression which also correlated poorly with PDK1 protein levels (data not shown). This observation is in accord with our previous data that suggested that PDK1 overexpression in this context arises from a post-translation mechanism.…”
Section: Discussioncontrasting
confidence: 42%
“…MEIS3 is up-regulated 65-fold by parasite infection and reversed with BW720c (confirmed by RT-PCR). A known direct target of MEIS3 is the 3-phosphoinositide-dependent protein kinase 1 (PDK1) involved in PI3-K-AKT signalling, engendering an anti-apoptotic role for MEIS3 [51]. Defined HOX targets are functionally wide ranging (reviewed in [52]) and include the CDK inhibitor p21, OPN (osteopontin), and bFGF (basic fibroblast growth factor).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse islets were isolated from 6- to 7-week-old wild-type C57/Bl6 males using collagenase digestion as previously described (32). Isolated islets were trypsinized (0.05% Trypsin) and plated as a monolayer onto poly- l -lysine-coated six-well dishes or four-well chambers, followed by transfection (Lipofectamine 2000) with 40 nmol/L antimiR-7a or control oligonucleotide.…”
Section: Methodsmentioning
confidence: 99%